(untitled) (Scientific journal of the Fergana State University, 2025)
This article reveals the essence of Fitrat’s concept of moral education, the issue of moral inclinations, and the importance of Fitrat’s spiritual and moral views in the education of young people for the development of the spiritual and educational sphere in our New Uzbekistan, and the use of them in building the foundations of the third Renaissance for today. The scientific heritage and philosophical teachings of our great thinkers, which deal with relations in social life, the relationship between state and religion, speak of their ability to create their own Eastern concepts of tolerance and tolerance.